2005
DOI: 10.1080/15459620500324727
|View full text |Cite
|
Sign up to set email alerts
|

Head-and-Face Anthropometric Survey of U.S. Respirator Users

Abstract: Sizing data generated by the military for use in fitting respirators have been the normative basis for commercial respirator sizing. Anthropometric data developed for males and females of military age in the 1950s and 1960s are still in use today and form the only comprehensive body of information available on this subject. The twofold objective of this study was to: (1) develop an anthropometric database detailing the face size distributions of respirator users using both traditional measurement methods and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 4 publications
1
104
0
3
Order By: Relevance
“…The averageness of the face and its symmetry serve as covariants in judging the perceived health of potential mates in sexual selection [30,28,24], and also the attractiveness of face [22,20]. As stated earlier, the male faces usuallye Statistics on head and face of American and Chinese adults reported in [39,40,9] have also confirmed this point. Concerning the face symmetry, in [23], Little et al reveal that the symmetry and sexual dimorphism from faces are related in humans, and suggest that they are biologically linked during face development.…”
Section: Methodology and Contributionssupporting
confidence: 63%
See 1 more Smart Citation
“…The averageness of the face and its symmetry serve as covariants in judging the perceived health of potential mates in sexual selection [30,28,24], and also the attractiveness of face [22,20]. As stated earlier, the male faces usuallye Statistics on head and face of American and Chinese adults reported in [39,40,9] have also confirmed this point. Concerning the face symmetry, in [23], Little et al reveal that the symmetry and sexual dimorphism from faces are related in humans, and suggest that they are biologically linked during face development.…”
Section: Methodology and Contributionssupporting
confidence: 63%
“…In addition to facial averageness and symmetry, the global spatiality and local gradient relates closely with sexual dimorphism in the face. As demonstrated in [39,40], the sexual dimorphism exhibits inequally in magnitude in different spatial parts of the face. Also, sexual dimprphism demonstrates the developmental stability [24] in faces.…”
Section: Methodology and Contributionsmentioning
confidence: 96%
“…A custom-built heated head was used to measure the thermal cooling properties of each helmet. The headform was based on head and face anthropomorphic measurements collected by Zhuang and Bradtmiller [8] who produced a 3D model of an average 50th percentile head. This model was 3D printed in ABS plastic which has a similar thermal conductivity to human skin, ensuring the heat would dissipate over the scalp at a realistic rate.…”
Section: Thermal Measurementsmentioning
confidence: 99%
“…The 2003 NIOSH nationwide survey of subjects obtained anthropometric data from several occupational backgrounds that utilized respirators on a regular basis: construction, manufacturing, firefighting, healthcare, law enforcement, and other occupational groups. These subjects were divided into three age strata (18-29, 30-44, and 45-65), two gender strata, and four racial/ethnic group strata [Caucasian, African-Americans, Hispanic, and Other (mainly Asian)] (Zhuang and Bradtmiller, 2005). Measurements of height, weight, neck circumference, and 18 facial dimensions were collected employing traditional anthropometric techniques.…”
Section: Subjectsmentioning
confidence: 99%
“…Zhuang et al have demonstrated that anthropometric data collected from military personnel in the 1960s are no longer reflective of the head-and-face anthropometric distribution of the current U.S. work force (Zhuang et al, 2004). To address the need for an updated anthropometric database, in 2003 NIOSH conducted a large scale head-and-face anthropometric survey of diverse, civilian respirator users obtaining traditional anthropometric measurements and laser surface scans (Zhuang and Bradtmiller, 2005). Using this data, ten facial dimensions relevant to respirator fit were chosen for defining a Principal Component Analysis (PCA) model, which divides the user population into five face-size categories (small, medium, large, long/narrow and short/ wide) (Zhuang et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%